The American journal of theology (University of Chicago Press], 1897)
Vols. 2-6 include "Theological and Semitic literature for 1898-1901, a bibliographical supplement to the American journal of theology and the American journal of Semitic languages and literatures. By W. Muss-Arnolt." (Separately paged)